The British essay from Addison to Dickens: a line of descent (Estudios Humanísticos. Filología, 1996)
It has become a commonplace for admirers of the well-known periodical essayists of the 18th century to hail their work as a cultural expression of national satisfaction with the Protestant succession, and with the economic and political settlements that laid the foundations for the House of Hanover. Alexander Chalmers' edition of the works of 'The British Essayists' (1803) testifies to this power of the form in the previous century, as well as the medium of its continuing influence into the next. Yet the standing of the periodical essay, as an important constitutive medium of a dominant culture, does not remain fixed, but undergoes a transformation before its eventual fragmentation in the late 19th Century. Even within Chalmer's collection, it is evident that the narrative persona of the essay is undergoing a decline in social status. With the handing down of both popularity and moral authority from Addison's genteel Whig "Spectator" and Henry Mackenzie's professional Edinburgh "Lounger" to the likes of Lamb's Cockney "Elia", Leigh Hunt's "Townsman" and the street-sketching personae of Thackeray and Dickens, the essayist's transformation from patrician to pavement artist is complete. Simultaneously, the force of the essay as a consolidator of British bourgeois ideals may be seen to diminish and reassert itself as a valuable agent of cultural criticism